Effect of 20 mg Fluorogestone Acetate (FGA) Sponges on Reproductive Parameters of Dairy Ovine Breeds in Southern Italy - Di Giorgio, Stefania; Vullo, Cecilia; Monti, Salvatore; Giambrone, Giada; Catone, Giuseppe; Marino, Gabriele; Panzera, Michele (Acta Scientiae Veterinariae, 2022)
Background: Intravaginal devices containing progestins are widely used for oestrus synchronization in sheep. Progestins give economic benefits to farmers but may have some limitations and the efficacy strictly depends on farm management. There are different devices, with different molecules (progesterone, medroxyprogesterone acetate, fluorogestone acetate), different dosages and long (12-14 days) and short-term (5-7 days) protocols. Experimental studies often include a limited number of animals and are held at different latitudes and with different system of management. To our knowledge, there are few reports in the literature on field application of the recently licensed 20 mg fluorogestone acetate (FGA) sponges in large ewe flocks, excluding the registration trials. Materials, Methods & Results: This study was designed to evaluate oestrous synchronization in 2 different breeds. A total of 1100 Lacaune (L) and 618 Sarda (S) were assigned to 8 groups, comparing multiparous (M) and nulliparous (N) and those synchronized in November (n) and May (m). The animals were assigned to 8 groups: LMm (n. 556), LNm (n. 180), SMm (n. 70), SNm (n. 32), LMn (n. 242), LNn (n. 222), SMn (n. 440) e SNn (n. 76). The intravaginal sponge was inserted for 14 days. At sponge withdrawal, eCG (400 IU, IM) was injected, and rams were joined into flocks 30 h later with a male/female ratio of 1:8. Transrectal ultrasonography was performed for pregnancy diagnosis after 30 days. Fertility parameters such as oestrus (OR), pregnancy (PR), lambing rates (LR) and prolificacy were calculated. Fisher exact test was used to compare parameters of each group with the corresponding and significance was set at P < 0.01. The use of intravaginal sponges in this study was easily performed in all animals. In nulliparous groups, digital insertion of the sponge, instead of the applicator, was preferred to avoid discomfort. Sponge loss was observed in 2% of treated ewes. At the removal of the sponge, mild vaginal contamination was observed in 90% of the ewes. Ultrasound finding of embryo resorption, pseudopregnancy and pyometra were found in rates under 2%. The loss of pregnancy ranged from 0 to 3.6% without significant differences among groups. The SMn group showed the best performances (0.91 OR, 0.88 PR, 0.85 LR), significantly higher than the other groups. Prolificacy was maximum in the LMn (1.68) and minimum in the SNm group (1.06), without significant differences among groups. Discussion: The 14-day regimen based on 20 mg FGA-releasing intravaginal devices is an easy and satisfactory synchronization regimen to improve the productivity and the fertility of sheep farm, and this can be managed and optimized in different breeding conditions. In this study, Sarda breed shows a good adaption to the environment with adult ewes giving the best results in reproductive season. However young Sarda ewes were less productive especially in non-breading season. Lacaune showed good reproductive potential, young and adult ewes responded to progestins in reproductive and non-reproductive season. It was confirmed that the reproductive performance is affected by season, age, and breed. This study encourages the breeding of indigenous breeds by implementing the management with modern technologies. The imported highly productive breeds, if well managed, can give a production less influenced by seasonal variables and age. Keywords: ewe, sheep, Lacaune, Sarda, oestrus synchronization, progestins, intravaginal device, indigenous breeds.